THE USE OF COMPUTERIZED SYSTEMS TO ROUTE VEHICLES ON ROAD TRANSPORT IN THE BLOK M BUS STATION USING ASYMETRIX TOOLBOOK II - Dhemes Kakung Wisnuntoro; Sutarno Skom, MMSi Sutarno Skom, MMSi (Jurnal Sistem Informasi, 2005)
Computer system applications to route vehicles on road transport is a multimediaapplication that contains about-route bus lines coming out of the Blok M bus stationwhich is packaged in a simple by using Asymetrix Toolbook II. It is expected thatinformation using this application can be useful for prospective passengers in theBlok M bus station, as for the multimedia element-element used in this application isimage, text, sound. Overall it was merged into a form of application that is easy tooperate, particularly for potential passengers. Simply by just clicking the cursor, thepassengers can see the information provided and listen to track bus route that willcome out of the Blok M bus station.